(3LGeY GdOhds - (3CMeO OOg , CMeO GHf dWa Gddg Gdehdhj GdQhej,J (B1113 (3g` s
(3ChdgG (B:s
(3CMeO Gddg MeO eJacQ ef eNdhbGJg s
(3BNQgG (B:s
(3HPcQ edhc GdTfcGQI CUMGH HYV HdGO aGQS s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B123s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B104 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YehejI (B(5019) s
Keywords: (3GdJGQjNs